TRADISI HARMONY IN NATURE DALAM AL-QUR’AN - Nur Afiyah Febriani (IBDA': Jurnal Kebudayaan Islam, 2012)
The controversy about the causes of the environment damage is spread out nowadays. The root of this problem is the people’s ideology about nature which is very stiff. Anthropocentrism people legitimate their action in natural exploitation. Meanwhile, if it is analyzed comprehensively, there are 800 verses of kawniyah verses in al-Qur’an that are related to the universe. This article tries to explore the verses which explain the ideal concept of interaction patterns and interconnection between man and the ecosystem. This paper shows that harmony-in nature vision of al-Qur’an possesses an eco-humanist theology.